1990
DOI: 10.2135/cropsci1990.0011183x003000020011x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Differences in Carbon Isotope Discrimination by Cowpea under Wet and Dry Field Conditions

Abstract: Theory and empirical evidence have demonstrated that 13C discrimination (∆) by leaves of C3 plants may be associated with intrinsic water‐use efficiency or productivity. Consequently, selection for ∆ has potential value in breeding plants with improved adaptation. This study evaluates genotypic differences in ∆ among cowpea [Vigna unguiculata (L.) Walp.] and genotype ✕ drought level interactions, and compares ∆ measured in leaves and grains. Sixty cowpea accessions were subjected to drought by growing them on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
2
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 0 publications
4
46
2
2
Order By: Relevance
“…between leaves and the corolla, they did not suggest substantial CO2 fixation via a pathway other than that typical of C3 (12,17). Hall et al (10) reported that 13C isotope discrimination for grains of cowpea [ Vigna unguiculata (L.) Walp.] was lower than that measured for subtending leaves and suggested that additional metabolic processes were responsible for the lower 13C discrimination in grains.…”
Section: Resultsmentioning
confidence: 99%
“…between leaves and the corolla, they did not suggest substantial CO2 fixation via a pathway other than that typical of C3 (12,17). Hall et al (10) reported that 13C isotope discrimination for grains of cowpea [ Vigna unguiculata (L.) Walp.] was lower than that measured for subtending leaves and suggested that additional metabolic processes were responsible for the lower 13C discrimination in grains.…”
Section: Resultsmentioning
confidence: 99%
“…Intraspecific variation in WUE (Briggs and Shantz, 1913;Peng and Krieg, 1992;Hammer et al, 1997;Xin et al, 2009) and RUE (Hammer and Vanderlip, 1989;Sinclair and Muchow, 1999;Hammer et al, 2010) has been reported in sorghum. Robust measurement of WUE and RUE in field studies is challenging, however, due to the lack of simple and rapid screening criteria and measurement techniques (Hall et al, 1990;Sinclair and Muchow, 1999) as well as the complexity of these traits. Consequently, there is limited knowledge of the genetic variability in both WUE and RUE in sorghum under field conditions.…”
mentioning
confidence: 99%
“…The second strategy was based on the intrinsic water-use efficiency, which should be associated with differences in the extent to which C 3 plants discriminate against 13 C (carbon isotope) compared with 12 C (∆) during CO 2 fixation. Measurements of plant composition of stable isotopes ( 13 C/ 12 C) in field conditions suggest a correlation between ∆ and genotype in cowpea (Hall et al, 1990;Hall et al, 1994).…”
Section: Introductionmentioning
confidence: 97%